THE INFLUENCE OF BRAND EQUITY OF E-COMMERCE BUSINESS ON CUSTOMER SATISFACTION: A STUDY OF MAKASSAR CITY RESIDENT - Suaib, Syarief Qayum (Jurnal Ilmiah Mahasiswa FEB, 2016)
The  purpose  of  this  research  is  to  examine  the  influence  of  Brand  Loyalty, Perceived Quality, Brand Awareness, and Brand Association on Customer Satisfaction of E-commerce business both partially and simultaneously on resident of Makassar City. Further purposive sampling technique was used in this research 125 respondents. The analysis tools are Multiple Linear Regression Analysis to determine the relationship between independent variable and dependent variable. The result of the study explained that Brand Loyalty, Perceived Quality, Brand Awareness, and Brand Association of the E- commerce have a significant effect partially and simultaniously to customer satisfaction. Therefore, the research result shows that Brand Awareness is the dominant variable that affects Customer Satisfaction. The result from this study can be applied to marketing strategy for the companies and interested parties for retaining and maximizing Brand Loyalty, Perceived Quality, Brand Awareness, and Brand Association to get a positive effect on the potential consumers that can lead to the fulfillment of Customer Satisfaction.   Keywords:  Brand  Loyalty,  Perceived  Quality,  Brand  Awareness,  Brand  Association, Customer Satisfaction.